Synthesis of branched alkyl substituted potential drug molecules active against prostate cancer - Çavuşoğlu, Nariye. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Prostate cancer is the second most common malignancy and age related cause of death among males especially in the western world. It is claimed that there is a relation between the probability of getting prostate cancer and a high androgen level. Testosterone and Dihydrotestosterone are two prostate cancer responsible androgens that are synthesized in both testes and adrenal gland. Hence, it is possible to get rid of the prostate cancer via inhibition of the synthesis of androgens both in testes and adrenal glands where CYP17 is the enzyme responsible for the biosynthesis of testosterone and dihydrotestosterone. In this study, synthesis of branched alkyl substituted potential drug molecules that might inhibit the CYP17 enzyme was targeted. Syntheses started with 4-amino-3- methoxybenzoic acid where first Fisher esterification method was applied. Then, the protection of the amine was achieved with AC2O. The double addition of n-BuLi to the ester was the key step in obtaining the branched alkyl substituted phenyl derivatives. After the deprotection of the amide, the resulting amines were coupled with naphthoic acid derivatives. For the coupling reactions two different approaches were undertaken. In the first one, naphthoic acid was converted to naphthoyl chloride with SOCl2 and then coupled with the amine derivative in the presence of triethylamine. The second approach was the in-situ conversion of the naphthoic acid derivatives to the corresponding naphthoyl bromides with PBr3 and then coupling with the amine derivatives in the presence of triethylamine in one pot. Similar transformations were also carried out with 4-amino-2- methoxybenzoic as the starting material. The final products were sent to Koç University for the biological testings. Docking and binding energy calculations of the final products were done by using AutoDock 4 computational program. It was observed that docking and binding energies of the final compounds obtained were better than the lead compound.
Keywords: Prostate -- Cancer -- Treatment.